2009
DOI: 10.3350/kjhep.2009.15.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Change in the serologic markers of hepatitis B after allogenic hematopoietic stem-cell transplantation

Abstract: Due to the adoptive immunity that was transferred from anti-HBs-positive donors, a seroconversion of HBsAg could occur in some HBsAg-positive recipients. HBsAg-positive donors had a lesser effect on the HBV serologic markers of recipients. However, a reactivation of HBV can occur following hematopoietic stem-cell transplantation in the cases of recipients or donors with a history of HBV, infection by an accompanying immune suppression. Therefore, prevention should be instigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…RS is also a testament to the long‐lived latent nature of covalently closed circular DNA (cccDNA) in hepatocytes, which enables HBV reactivation after loss of immunological control . Published studies have shown that RS does not occur in patients who have received donor stem cells with positive antiHBsAb, which have been shown to have protective effects , and indeed the potential exists for HBsAg seroconversion in the recipient owing to adoptive immunity from the donor .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RS is also a testament to the long‐lived latent nature of covalently closed circular DNA (cccDNA) in hepatocytes, which enables HBV reactivation after loss of immunological control . Published studies have shown that RS does not occur in patients who have received donor stem cells with positive antiHBsAb, which have been shown to have protective effects , and indeed the potential exists for HBsAg seroconversion in the recipient owing to adoptive immunity from the donor .…”
Section: Discussionmentioning
confidence: 99%
“…As such, we were unable to fully account for the finding of persistent antiHBcAb positivity after allo‐HSCT with a determination of clinical risk factors contributing to HBV exposure. In addition, the lack of routine regular testing of both patient and donor antiHBsAb levels made it difficult to determine the relationship and potential protective effect of antiHBsAbs, as reported in published studies .…”
Section: Discussionmentioning
confidence: 99%